TG-Interacting Factor Expression in Leiomyoma Compared to Myometrium - Ho, Jason Yen-Ping (2009)
OBJECTIVE: To investigate the expression of TG-interacting factor (TGIF), a Smad transcriptional corepressor, in leiomyoma and matched myometrial tissue samples and the effect of TGIF overexpression in myometrial cells. DESIGN: Experimental study. SETTING: Tertiary university hospital. PATIENT(S): Uterine leiomyoma and myometrial tissues from sixteen patients. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): The distribution of TGIF in leiomyoma and myometrial tissues by immunohistochemistry stain. mRAN and protein expression levels by real-time quantitative polymerase chain-reaction (QPCR) and Western blot. Transcriptional regulation of TGIF in myometrial cells with over-expressed TGIF. RESULT(S): TGIF is present in the smooth muscle cells of the leiomyoma and the myometrium but not in the extracellular matrix. TGIF mRNA and protein expressions were significantly higher in the leiomyoma compared to the matched, unaffected myometrial tissues in both phases of the menstrual cycle. There were no differences in mRNA or protein expression throughout the menstrual cycle. Overexpression of TGIF protein in myometrial cells significantly suppressed up-regulation of plasminogen activator inhibitor (PAI-1) induced by TGF-β1 treatment. CONCLUSION(S): TGIF expression is increased in leiomyoma compared to myometrium. This increase in TGIF expression is not affected by endogenous ovarian hormones. TGIF is a potential repressor of TGF-β pathways in myometrial cells.